TRANSLATING ANIMATION BY EKI N. F., DEDDY OTARA, AND ZULFA ASLIHA ENTITLED “EYANG HABIBIE” ADIT AND SOPO JARWO - Cahyana, Lanang Mahardhika; Setiawan, Kristianto; Sudja’ie, Mimien Aminah (Program Studi Diploma Tiga Bahasa Inggris Fakultas Ilmu Budaya Unsoed, 2021)
This article is entitled Translating Animation by Eki N. F., Deddy Otara, and Zulfa Asliha entitled “Eyang Habibie” Adit Sopo Jarwo. The purpose of translates Adit Sopo Jarwo’s animation